2013
DOI: 10.1007/s00415-013-7037-5
|View full text |Cite|
|
Sign up to set email alerts
|

Ambulatory activity in incident Parkinson’s: more than meets the eye?

Abstract: Physical activity is important for people with Parkinson's disease (PD) to improve disease-specific impairment and ameliorate secondary consequences related to deconditioning. Activity may also have a neuroprotective role if instigated early. Ambulatory activity has not been examined in incident PD. Eighty-nine newly diagnosed PD cases [mean (SD) age 67.3 (9.9) years] and 97 controls [mean (SD) 69.2 (7.7) years] wore an activity monitor (activPAL™) for 7 days. Volume, pattern and variability outcomes were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
151
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(165 citation statements)
references
References 43 publications
11
151
2
1
Order By: Relevance
“…After analyzing a massive amount of data, researchers found that a change in tremor was a significant predictor of change in UPDRS (P=0.047) (32). The AHTD consisted of a series of motor tasks that the participants could perform at home, while another activity monitor-activPAL, was able to collect data of daily living activity (33). Eighty-nine newly diagnosed PD patients and 97 controls wore an activPAL for 7 days.…”
Section: Continuous Monitoring In Daily Activitiesmentioning
confidence: 99%
“…After analyzing a massive amount of data, researchers found that a change in tremor was a significant predictor of change in UPDRS (P=0.047) (32). The AHTD consisted of a series of motor tasks that the participants could perform at home, while another activity monitor-activPAL, was able to collect data of daily living activity (33). Eighty-nine newly diagnosed PD patients and 97 controls wore an activPAL for 7 days.…”
Section: Continuous Monitoring In Daily Activitiesmentioning
confidence: 99%
“…Patterns were defined according to (i) total number of bouts per day for each behavior (e.g., number of lying bouts); (ii) mean bout length for each behavior per day (e.g., mean lying bout length), where a bout, similar to other studies [13,25], is defined as any period of time spent in a certain behavior.…”
Section: Methodsmentioning
confidence: 99%
“…Parkinson's disease (PD) is a neurodegenerative condition that exerts a negative influence on postural control and mobility, predominantly among older adults, affecting mobility and increasing the risk of slipping, tripping and falls (1) . According to Sanfelice (2) , the diagnosis of PD in the early phases is not easy, but the classic symptoms of tremor, stiffness and bradykinesis can allow the diagnosis on the first evaluation.…”
Section: Introductionmentioning
confidence: 99%